Charakter prawny składki na ubezpieczenie zdrowotne jako źródła finansowania świadczeń opieki zdrowotnej - Lenio, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
This paper describes the legal characteristics of health care taxation as a form financing of the health system. The attributes of this tax are not covered by Polish legal literature. Therefore it is justified to consider the research on this subject. Features of this financial charge should be examined in two ways: regarding its goal and regarding its structure. In this article health care taxation is described on the basis of Article 217 of the Polish Constitution. There are also presented the differences from regular fiscal taxes. The author recognizes the basic traits of health care taxation: it is public, compulsory and has a specific goal that differentiates it from other taxes.
Keywords: ubezpieczenie zdrowotne; składka; źródło finansowania; świadczenia opieki zdrowotnej